Statistical Abstract of Madhya Pradesh 1958-59 - Planning Commission (Planning Commission, 1958)
Except where otherwise stated all the statistics contained in this Abstract relate to the New State of Madhya Pradesh as reorganised on the basis of States Reorganisation Act, 1956. Although necessary adjustments have been made wherever feasible for the transfers of Sunel Tappa from the former Mandsaur District of Madhya Bharat region to Kotali District of Rajasthan and Sironj sub-division (Sunel and Later tahsils) of Kotah district of Rajasthan to Vidisha district of Madhya Bharat region, in certain cases the figures for periods earlier to the calendar year 1956 and financial or agricultural year 1955-56 could not be adjusted for want of required breakdowns.
Directorate of Economics and Statistics Madhya Pradesh